Углубленный курс информатики учебное пособие - Иванчина Э. Д. Эмилия Дмитриевна; Чузлов В. А. Вячеслав Алексеевич; Назарова Г. Ю. Галина Юрьевна; Белинская Н. С. Наталия Сергеевна; Долганов И. М. Игорь Михайлович; Долганова И. О. Ирэна Олеговна (Томск, Изд-то ТПУ, 2017)
Заглавие с титульного экрана